Roles of External Forcing and Internal Variability in Winter Precipitation Changes Over Central Asia - Mengyuan Yao; Haosu Tang; Gang Huang (Earth's Future, 2025)
Abstract Winter Central Asian precipitation (WCAP) is increasingly replacing snowfall as a critical water resource under global warming. Observations show a decline in WCAP from 1891 to 1946, followed by a recovery from 1947 to the recent decade. However, the relative contributions of external forcing and internal variability to these changes remain unclear. By analyzing observations and climate model simulations, this study finds that greenhouse gas forcing favors increasing WCAP, potentially offsetting drying trends driven by anthropogenic aerosols. Internal variability, primarily the phase transition of Atlantic Multidecadal Variability (AMV), plays a dominant role in shaping WCAP trends. The AMV‐induced Rossby wave train, sustained by extracting baroclinic energy from the background mean flow, triggers barotropic atmospheric circulation anomalies that modulate WCAP. The cold‐to‐warm AMV phase transition (1891–1946) weakened the externally forced upward precipitation trend, reducing it from 0.19 to −0.20 mm month−1 decade−1. In contrast, the warm‐to‐cold phase transition (1947–1997) amplified the externally forced precipitation trend, increasing it from 0.28 to 0.99 mm month−1 decade−1. Under the high‐emission future scenario, the time of emergence of externally driven WCAP increases is projected to occur between 2030 and 2060, at least a decade earlier than the post‐2060 timeline projected under the medium‐emission scenario. These findings underscore the critical role of AMV in shaping WCAP variability and highlight the necessity of emission reductions to delay the time when externally driven precipitation increases exceed the region's adaptive capacity.